METHODS FOR DIAGNOSING HEARING LOSS IN CHILDREN IN THE FIRST YEARS OF LIFE - Kodirov Khusanboy Solievich (SAMARALI TA’LIM VA BARQAROR INNOVATSIYALAR JURNALI, 2025)
The aim of the study is a comparative analysis of objective methods for studying the auditory function in children and identifying factors influencing the results of the study. Patients and methods. The hearing was studied in 473 children aged 3 months to 5 years suffering from sensorineural hearing loss and deafness. The comparison group consisted of 30 children with normal hearing. Along with the standard clinical examination of the ENT organs, all children underwent tympanometry and reflexometry, a study of delayed evoked otoacoustic emission and otoacoustic emission at the frequency of the distortion product, registration of short-latency auditory evoked potentials and auditory potentials to a continuously modulated tone (ASSR).